Adaptational Mechanisms of Epiphytic Orchids: A Review - De, L. C.; Biswas, S. S. (International Journal of Bio-resource and Stress Management, 2022)
Orchidaceae belongs to the 84 families of vascular plants that cover species following the epiphytic life pattern. Adaptations are specialized mechanisms that permit a plant or animal to live in a particular area or habitat. Adaptational mechanisms in plant morphology are essential for the transition to an epiphytic canopy habitat. Orchids have specific adaptational mechanisms in the roots, stems, leaves, flowers, seed and other physiological processes. Under water scarcity, these orchids have developed pseudobulbs, an energy, water, and nutrient storage bulb for adaptations.A wax coating covering the surface of the leaf, also prevents evaporation and gas exchange in drier or hotter climate.Epiphytic orchids have adequate root systems to enable them to grow in a poor nutrient environment when they grow at slow rate. In such cases, velamen of orchids helps to absorb water and also help to absorb nutrients from rainfall. Orchid roots are adapted to cling to trees. Orchid seeds do not have endosperm and require a fungal association with mycorrhiza to provide its energy till the development of roots and leaves. This symbiotic feature is another adaption to make the orchid seed to travel longer and further distances for survival. In comparison to the activity of C3 photosynthesis, crassulacean acid metabolism (CAM) in many epiphytes plays a vital role in improving carbon gains and water use. In this review, specialized adaptations of some commercial orchid genera namely Dendrobium, Cymbidium, Phalaenopsis, Cattleya, Oncidium, Epidendrum and Paphiopedilum are discussed in detail.